2022
DOI: 10.17557/tjfc.1050448
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Variability, Heritability and Genetic Advance in Pod Yield, Yield Components, Oil and Protein Content of Peanut Varieties

Abstract: In this study, genetic and environmental variability, broad-sense heritability, genetic advance and correlation coefficients of pod yield, yield components, oil and protein content of ten registered peanut varieties were examined. Year (Y), location (L), year x location interaction (Y x L), genotype (G), genotype x year interaction (G x Y), genotype x location interaction (G x L) and genotype x year x location interaction (G x Y x L) were significant, but G x Y for shelling percentage was not significant. Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Although both cultivars presented lower yield than their average potential (4500 kg/ha), it was similar to the range reported in the literature (3240–5856 kg/ha for IAC OL3 and 3029–5280 kg/ha for IAC503) . The peanut yield varies according to genetics (cultivars and genotypes) and environmental conditions such as temperature, humidity, rainfall, diseases, and pests . The 2017–2018 growing season had approximately 770 mm of precipitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both cultivars presented lower yield than their average potential (4500 kg/ha), it was similar to the range reported in the literature (3240–5856 kg/ha for IAC OL3 and 3029–5280 kg/ha for IAC503) . The peanut yield varies according to genetics (cultivars and genotypes) and environmental conditions such as temperature, humidity, rainfall, diseases, and pests . The 2017–2018 growing season had approximately 770 mm of precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…4 The peanut yield varies according to genetics (cultivars and genotypes) and environmental conditions such as temperature, humidity, rainfall, diseases, and pests. 36 The 2017−2018 growing season had approximately 770 mm of precipitation. Considering that higher yields require 500 to 700 mm of water, 4 the lower mean yield results in the present study may be related to another environmental condition.…”
Section: Peanut Yield Shelling Percentage and Gradesmentioning
confidence: 99%
“…The genetic advance was calculated using the formulae suggested by Johnson et al [21] as Genetic advance as percent of mean: Genetic advance in percentage of mean was calculated using the formula given by Robinson et al [20]; GAM 100 GA X = where GAM = genetic advance as percent of mean, GA = genetic advance under selection, and X = grand mean of the trait. Genetic advance as percent mean was categorized as low (0-10%), moderate (10-20%), and high (≥20%) as given by Killi and Beycioğlu [15] and Johnson et al [21]. https://www.academia.edu/journals/2/academia_biology/about https://doi.org/10.20935/AcadBiol6085 ACADEMIA BIOLOGY 2023, 1…”
Section: Genetic Advancementioning
confidence: 99%
“…Groundnut nutrient composition improvement is not only dependent on the magnitude of the phenotypic variability but also how those desirable nutritive components are inherited. The success of any crop improvement program essentially depends on the magnitude of the genetic variability present in the crop species [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…(1993) reported on variability in fatty acid composition in 13 germplasm lines under 12 environments (different combinations of year across rainy/post‐rainy seasons) and found that all effects (including G, E, and G × E) significantly contributed to variation in oil and fatty acid composition. More recently, significant interaction effects on peanut oil and protein content were reported from 10 registered cultivars evaluated at three locations for 2 years (Killi & Beycioglu, 2022).…”
Section: Introductionmentioning
confidence: 99%